2011
DOI: 10.1182/blood-2011-07-368084
|View full text |Cite
|
Sign up to set email alerts
|

The CXCR4 antagonist plerixafor corrects panleukopenia in patients with WHIM syndrome

Abstract: WHIM syndrome is a rare congenital immunodeficiency disorder characterized by warts, hypogammaglobulinemia, infections, and myelokathexis (neutropenia because of impaired egress from the BM); most patients also have severe panleukopenia. Because WHIM syndrome is caused by mutations in the chemokine receptor CXCR4 that result in increased agonist-dependent signaling, we hypothesized that the CXCR4 antagonist plerixafor (Mozobil [Genyzme Corporation], AMD3100), might be an effective treatment. To test this, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 29 publications
10
113
1
2
Order By: Relevance
“…Three unrelated white adults with WHIM syndrome were recruited: a 44-year-old female (P1), a 30-year-old female (P2), and a 51-year-old male (P3). P1 was first reported in Wetzler et al, 3 whereas P2 and P3 were first reported in McDermott et al 18 All 3 patients had the 4 major clinical features of WHIM syndrome and were heterozygous for CXCR4 R334X , the most common mutation in the disease, which truncates the receptor by 19 amino acids. Each had previously participated in a 7-day, phase 1 dose-escalation study of plerixafor at the National Institutes of Health reported previously and had a hematologic response to the drug with an increase in most subsets of circulating leukocytes without significant side effects.…”
Section: Methods Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three unrelated white adults with WHIM syndrome were recruited: a 44-year-old female (P1), a 30-year-old female (P2), and a 51-year-old male (P3). P1 was first reported in Wetzler et al, 3 whereas P2 and P3 were first reported in McDermott et al 18 All 3 patients had the 4 major clinical features of WHIM syndrome and were heterozygous for CXCR4 R334X , the most common mutation in the disease, which truncates the receptor by 19 amino acids. Each had previously participated in a 7-day, phase 1 dose-escalation study of plerixafor at the National Institutes of Health reported previously and had a hematologic response to the drug with an increase in most subsets of circulating leukocytes without significant side effects.…”
Section: Methods Patientsmentioning
confidence: 99%
“…Specifically, in two phase 1 clinical trials lasting 1 to 2 weeks in patients with WHIM syndrome, plerixafor was able to safely and rapidly increase absolute lymphocyte, monocyte, and neutrophil counts in the peripheral blood in a dose-dependent manner, including at the lowest dose tested, 0.02 mg/kg per day by subcutaneous administration, which is 8% of the FDA-approved dose for stem cell mobilization (0.24 mg/kg per day). 17,18 These trials were not designed to test the effect of the The online version of this article contains a data supplement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also be informative to test the changes in leukocyte mobilization stimulated by AMD3100. In mice and humans, AMD3100 is capable of mobilizing T cells (and other leukocytes), which may have also contributed to the resistance phenotype observed in these mice [29,55,56].…”
Section: Cxcr4mentioning
confidence: 99%
“…Early reports have shown that plerixafor reversed leukopenia in WHIM patients. 41,42 More recently, a phase 1 clinical trial of long-term, low-dose therapy of WHIM syndrome patients with plerixafor showed lack of toxicity and durably increased circulating leukocytes. The concept of targeted CXCR4 inhibition in WHIM patients warrants further clinical studies.…”
Section: Scn7 (Csf3r)mentioning
confidence: 99%